Sistematización del riego por aspersión para el cultivo de cacao (Theobroma cacao L) en el área de agrícola de la ESPAM MFL - Palma Alcívar, Gema Teresa (2013)
This paper describes the automation of an irrigation system for the cultivation of cacao (Theobroma cacao L) of MFL ESPAM, before undertaking the systematic gathered information about crop water needs, then designed the main circuit DipTrace establishing the necessary components for assembly; thereof also the creation of source code for the PIC microcontroller Compiler CSS, which is validated by Proteus which found through simulation indicated logical operation device to finish programming and physical tests were made to turn the device on the valve station located in the School of Agriculture. The determination of the elements is vital for no delays and eases the design of the plate for proper implementation of the components in it and create conditions for the automation of the irrigation system through programming, the same as for validating operation are necessary testing.